The Exploitation of Communication Based Technology in Terms of Assisting the Students of the Hellenic Open University Towards the Development of their Written Assignments - Koukousouri, Vasiliki; Karaoulanis, Andreas (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
The purpose of this research is to investigate the views of the postgraduate students of the Hellenic Open University during the 2016-17 academic year on the possibilities of using internet based platforms and computer technology in general for the preparation of their written work in such a distance learning degree. Our sample was students 24 women and 6 men. All students in the same degree in the above mentioned academic year. Students were asked to complete a written questionnaire that was posted on the internet, while they were ensured for their anonymity. Data analysis was done by following a quantitative approach via the usage of the SPSS24 statistical software. The most important findings of the research were that of all forms of internet and computer based technology that was used in order to assist students during their studies, the forum, the emails and the usage of phone conversations with students and lectures were the ones that were mostly related with their written assignments. In terms of their educational needs in general, they were covered by email, forums, telephone communication and they also chose to videoconferencing. Generally speaking, they have shown that internet and computer technology are essential in distance learning education. Finally, students wanted to improve their communication with their lectures, would like to increase their telephone communication with them and to give answers to their questions via the forum usage.